Meru Info -Kiosk - Wanjohi Njeri Doris; Wanjohi Njeri Doris (Meru: Wanjohi Njeri Doris, 2013)
This document contains the detailed descriptions and overview of the system developed as an information kiosk for the Meru county ,the information kiosk avails information to users and also provides a forum for interacting with the information.The system is both web based and mobile based and it enhances use of technology by providing forum for users to share information in the county and also to access the information provided by other users.It provides user level access and administrator level; access for the various users.The system aims to alleviate varoius problem in the county originating from inaccessibility.
A project submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science.